Corporate Financing Strategy and Its Impact on Firm Performance: a Critical Systematic Literature Review - Rizki, Muhammad Hilman; Ajis , Muhammad; Astrilia , Herfiana; Pitriani , Nurul; Andarini , Afini Dwina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study critically examines the relationship between capital structure, leverage, and initial public offerings (IPOs) on firm performance through a systematic literature review. Using Scopus-indexed articles and keyword combinations such as “capital structure,” “leverage,” and “initial public offering” 29 studies were identified and analyzed. The findings reveal that each factor plays a distinct role in influencing firm performance. While capital structure and leverage significantly affect long-term performance and financial stability, IPOs introduce unique dynamics in terms of market valuation and stakeholder expectations. This review highlights key gaps in existing research, including the need for more comprehensive methodologies to explore these interconnected factors. The study contributes an integrative perspective for future research and strategic decision-making in financial management.